Mengkoordinir Ragam Format Acara Dakwah - Erwan Efendi; Isnaini Miranda Ginting; Hafidz Umri; Ilham Ramadhan (Fakultas Tarbiyah IAI Nasional Laa Roiba, 2023)
Dakwah (tabligh) is a call to invite to the path of Allah SWT, in the era towards 5.0, of course, the development of proselytizing is also increasing. Good proselytizing must be prepared before it begins. In the ongoing proselytizing (tabligh) component, from one point of view this is a turn of empowerment events, as a sign of the intense intensity of the region starting to develop again (Setiawan et al., 2021) However, subjectively the exercises as in the taklim assemblies are not as much as fully active definitive objectives of the proselytizing movement itself and do not make much improvement to the da'wah ummat (mad'u). So a unique system is needed for the practice of proselytizing to emerge on a broader understanding of Islamic lessons that touch on the components of human life and existence for today's mad'u. The word system started from the old Greek style of